2007
DOI: 10.1051/gse:2007036
|View full text |Cite
|
Sign up to set email alerts
|

Estimation by simulation of the efficiency of the French marker-assisted selection program in dairy cattle(Open Access publication)

Abstract: -. This improvement was also observed by analysis of information content for young candidates. The gain of MAS reliability with respect to classical selection was larger for sons of sires with genotyped progeny daughters with records. Finally, it was shown that when superiority of MAS over classical selection was estimated with daughter yield deviations obtained after progeny test instead of true breeding values, the gain was underestimated.marker-assisted selection / simulation / efficiency / dairy cattle

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
0
10
0
3
Order By: Relevance
“…The benefits of high densities are seen more clearly when assuming very large populations involving several families, as illustrated by Guillaume et al (2008) in a dairy cattle dataset. They found a substantial gain in reliability, by replacing microsatellite markers by 10 SNPs within a 1-cM bracket around the QTL, from 43 to 79 % in comparison to classical selection.…”
Section: Level Of Variation For the Targeted Traitsmentioning
confidence: 91%
See 1 more Smart Citation
“…The benefits of high densities are seen more clearly when assuming very large populations involving several families, as illustrated by Guillaume et al (2008) in a dairy cattle dataset. They found a substantial gain in reliability, by replacing microsatellite markers by 10 SNPs within a 1-cM bracket around the QTL, from 43 to 79 % in comparison to classical selection.…”
Section: Level Of Variation For the Targeted Traitsmentioning
confidence: 91%
“…For a given number of QTLs, a scenario with even QTL effects led to lower MAS efficiency compared to QTL effects in geometric distributions, with differences being particularly noticeable within an h 2 range of 0.15~0.2. With a pedigree-based dairy cattle dataset, Guillaume et al (2008) found that MAS was more beneficial when there are fewer QTLs with large effects, with situations close to the infinitesimal model being less favorable for MAS. Geometrical or Lshape distributions of QTL effects are thought to reflect what is observed for many quantitative traits (Kearsey and Farquhar 1998;Bernardo 2008), in livestock (Silva et al 2011) and in crops (Truntzler et al 2010).…”
Section: Level Of Variation For the Targeted Traitsmentioning
confidence: 96%
“…These markers were selected previously in two different experimental designs: the French MAS program (e.g. Guillaume et al 2008) and a Normande-Holstein F-2 design implemented in an experimental farm (Larroque et al 2007). The mean number of markers per chromosome was 5.1, ranging from 2 to 10.…”
Section: Genotyping Datamentioning
confidence: 99%
“…The multiple trait derivative free restricted maximum likelihood (MTDFREML) [26] software has been modified to facilitate the prediction of breeding values using GRMs [27]. While GS is now being tested within commercial dairy cattle populations [14,28,29], traditional progeny testing schemes used to achieve high accuracies on the bulls released for widespread use are being modified to reflect the gains in selection response that are possible when bulls, at birth, have estimates of genetic merit with accuracies that are similar to those achieved, on average, with 11 daughter equivalents [14]. …”
Section: Introductionmentioning
confidence: 99%